PERENCANAAN DRAINASE DAN SUMUR RESAPAN PERUMAHAN PALM HILL CILEGON, JAWA BARAT - Miftakhul Yaqin, Mohammad Zenurianto, Suhartono (Jurusan Teknik Sipil, Politeknik Negeri Malang, 2015)
Palm Hill housing must be completed with a proper drainage system and infiltration well to prevent it from surface run off water. The objective of the study is to design the drainage system and the infiltration well completed with its implementation time and budget.Topograpical map was needed to find out the elevation. Rainfall data from 3 nearby stations of Ciruas, Petir, and Serang were calculated through Log Pearson III method to find out the proposed rain fall at 10-year time reture. Waste water discharge was estimated 80% out of 364 houses. Cumulative discharge was resulted from the addition of run off to infiltration well to waste water discharges. The result was processed using Manning formula to design the culvert dimension.The calculations result in 6 different culvert dimensions,1 types of culvert,358 infiltration well, 277 work days at IDR2,954,079,288Keywords: drainage system, infiltration well